Experimental Analysis of Bearing Cup Used In Automobiles by Heat Treatment Processes - Paresh S. Pawar; Dr. S. B. Zope; Prof. Patil A. R (International Journal of Innovations in Engineering Research and Technology, 2021)
In Automobile Propeller Shaft assembly, bearing cup assembly get cracked during operation in universal joint. This was highest rejection; hence it was decided to eliminate bearing cup failure in drive shaft assembly with effective solution. Investigation of failed part reveals that due to improper heattreatment like through hardening bearing cup get brittle. Differentiate surface treatment like carburizing, nitriding and hardening were suggested and comparative evaluation was made on the basis of chemical analysis, hardness test, microstructure study etc. After evaluating all the processes result reveals that carburizing process as heat treatment process for bearing cup assembly has given good results over earlier process of surface hardening.